2014
DOI: 10.1590/s1679-78252014000500001
|View full text |Cite
|
Sign up to set email alerts
|

Damage identification from uniform load surface using continuous and stationary wavelet transforms

Abstract: Derived from flexibility matrix, Uniform Load Surface (ULS) is used to identify damages in beam-type structures. This method is beneficial in terms of more participating the lower order modes and having less prone to noise and irregularities in the measured data in comparison with the original flexibility matrix technique. Therefore, these characteristics make this approach a practical tool in the field of damage identification. This paper presents a procedure to employ stationary wavelet transform multi-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Their method implements SWT to refine the modal shapes and then look for damage applying CWT to the refined modal shape. Masoumi and Ashory [31] made numerical and experimental studies on this method to localize cracks. However, they only took into account the first modal shape in their calculations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their method implements SWT to refine the modal shapes and then look for damage applying CWT to the refined modal shape. Masoumi and Ashory [31] made numerical and experimental studies on this method to localize cracks. However, they only took into account the first modal shape in their calculations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their respective SMSs yielded by equation (3) occupy smaller-, intermediate-, and greater-scale contents in light of the inverse relation between frequency and scale in a wavelet definition (Mallat and Hwang, 1992;Masoumi and Ashory, 2014). That being the case, the damage component can be managed by successively adjusting the scale parameter s in equation (3).…”
Section: Smss For Isolating Damage Componentmentioning
confidence: 99%
“…Unfortunately, a pristine counterpart is commonly unavailable in real-life delamination diagnosis, severely hampering the feasibility of delamination detection. To address this limitation, this study focuses on developing a non-baseline scheme for identifying delamination by fully integrating noncontact high-resolution vibration measurement techniques and advanced signal processing theories including fractal analysis (Cao et al, 2005(Cao et al, , 2006Farhidzadeh et al, 2013;Moustafa et al, 2014;Moustafa and Salamone, 2012) and wavelet transforms (Cao and Qiao, 2008;Masoumi and Ashory, 2014;Quek et al, 2001;Sohn et al, 2004;Wang and Deng, 1999;Wei et al, 2004;Wu and Wang, 2011). First, two new concepts, scale mode shape (SMS) and scale waveform dimension (SWD), are elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…Masoumi, et al [10] identified the damage location using the continuous and the stationary wavelet transforms on the uniform load surface. Janeliukstis et al [11] detected the damage in polymer composite beams based on spatial continuous wavelet transform.…”
Section: Introductionmentioning
confidence: 99%